2014
DOI: 10.1111/1574-6941.12298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wastewater disposal on the bacterial and archaeal community of sea sediment in an industrial area in China

Abstract: Human activities usually leave footprints in the environment. By using 454 pyrosequencing, the impact of effluent from an industrial park on the coastal microecology in Hangzhou Bay, China, was interpreted by analysing the microbial communities of the activated sludge from three wastewater treatment plants and the sediment from the effluent receiving area. Based on richness and biodiversity, the sediments were more diversified than the activated sludge, although the seawater environment was highly contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…With regard to the archaea, Euryarchaeota represented 94.6% of the total number of sequences, while Thaumarchaeota represented 5.4%, respectively. This is in line with previous studies where Euryarchaeota were found to dominate the archaeal community in activated sludge from municipal WWTPs (Ju et al., ; Zhang et al., ). Further, as also noticed in previous studies on microbial communities in activated sludge (Hu et al., ; Saunders et al., ; Wang et al., ; Wei et al., ; Yang et al., ; Zhang et al., ; Zhao et al., ), Proteobacteria was the most abundant bacterial phylum detected (44.3% of the total number of sequences), followed by Bacteroidetes (24.8%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…With regard to the archaea, Euryarchaeota represented 94.6% of the total number of sequences, while Thaumarchaeota represented 5.4%, respectively. This is in line with previous studies where Euryarchaeota were found to dominate the archaeal community in activated sludge from municipal WWTPs (Ju et al., ; Zhang et al., ). Further, as also noticed in previous studies on microbial communities in activated sludge (Hu et al., ; Saunders et al., ; Wang et al., ; Wei et al., ; Yang et al., ; Zhang et al., ; Zhao et al., ), Proteobacteria was the most abundant bacterial phylum detected (44.3% of the total number of sequences), followed by Bacteroidetes (24.8%).…”
Section: Resultssupporting
confidence: 93%
“…Notably, a great number of OTUs (40) belonging to the genus Planctomyces (Planctomycetes) were specifically found in textile WWTPs, suggesting that these bacteria are well‐adapted to the conditions encountered in textile wastewater treatment systems, which, for example, are typically characterized by a high salt concentration. As such, these findings are in line with previous research showing that these bacteria can thrive in salt‐rich environments (Zhang et al., ). Additionally, members of the genera Leucobacter (Actinobacteria) and Hydrogenophaga (Proteobacteria) were predominantly found in the textile‐activated sludge samples.…”
Section: Resultssupporting
confidence: 92%
“…As the archaeal primer 344F has often been used for detecting archaea in a variety of environmental samples (Zhang et al, 2014; Fontana et al, 2016), we further analyzed its coverage using TestProbe 3.0 (Klindworth et al, 2013) and the SILVA database SSU132 (Quast et al, 2013). The results revealed 73.2% coverage of the archaeal domain, a high coverage of the Euryarchaeota phylum (93.8%) and the genera within, especially Methanobrevibacter with 96.1% coverage, Methanosphaera with 89.9% and Methanomassiliicoccus with 100%.…”
Section: Resultsmentioning
confidence: 99%
“…The class Wosearchaeia showed variable coverage between 65.2% and 89.5%. As the archaeal primer 344F has often been used for detecting archaea in a variety of environmental samples (Fontana et al, 2016;Zhang et al, 2014), we took a closer look on its coverage capacity using the TestProbe 3.0 (Klindworth et al, 2013) and the SILVA database SSU132 .…”
Section: Resultsmentioning
confidence: 99%